PENGARUH EDUKASI MENGGUNAKAN MEDIA LEAFLET TERHADAP PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG KEKURANGAN ENERGI KRONIS (KEK) DI PUSKESMAS SELATBARU KABUPATEN BENGKALIS - Savitri, Desy; Susanti, Komaria; Ekdeni Aifa, Wira; Oktora Sri, Ary (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Chronic Energy Deficiency (CED) in pregnant women is a condition with an upper arm circumference of less than 23.5 cm, or a weight gain of <9 kg during pregnancy. Knowledge will greatly influence the behavior of pregnant women. This behavioral factor is what makes pregnant women less aware of the benefits of food intake, especially nutrition during pregnancy. Another influencing factor is the attitude of a pregnant mother. One way that can be used to increase the knowledge and attitudes of pregnant women is by conducting health education using leaflet media. Leaflet media can provide stimulation to two human senses, namely sight. Health education carried out in a structured and consistent manner can provide effective information for a person. The aim of this research is to determine the influence of education using leaflet media on the knowledge and attitudes of pregnant women regarding KEK at the Selatbaru Community Health Center, Bengkalis Regency. This type of research is quasi-experimental with a one group pre-test and post-test design. The population in this study was all 25 KEK pregnant women in August – September 2024. The sample in the study was 15 KEK pregnant women. The sampling technique uses purposive sampling. The instrument used was a questionnaire. Research result. There is an influence of education using leaflet media on pregnant women's knowledge about KEK at the Selatbaru Health Center, Bengkalis Regency with a p-value = 0.009 and there is an influence of education using leaflet media on the attitudes of pregnant women about KEK at the Selatbaru Community Health Center, Bengkalis Regency with a p-value = 0.000. In conclusion, there is an influence of education using leaflet media on the knowledge and attitudes of pregnant women regarding KEK at the Selatbaru Community Health Center, Bengkalis Regency. Suggestions for pregnant women are to more regularly check their pregnancies with health workers and actively participate in counseling conducted by health workers to obtain information regarding nutrition during pregnancy. Keywords: Education, Leaflet Media, Knowledge and Attitudes of Pregnant Women